One Health economics to confront disease threats - Machalaba, C.; Smith, K.M.; Awada, L.; Berry, K.; Berthe, F.; Bouley, T.A.; Bruce, M.; Abrahantes, J.C.; El Turabi, A.; Feferholtz, Y.; Flynn, L.; Fournié, G.; et al. (Oxford University Press, 2017)
Global economic impacts of epidemics suggest high return on investment in prevention and One Health capacity. However, such investments remain limited, contributing to persistent endemic diseases and vulnerability to emerging ones. An interdisciplinary workshop explored methods for country-level analysis of added value of One Health approaches to disease control. Key recommendations include: 1. systems thinking to identify risks and mitigation options for decision-making under uncertainty; 2. multisectoral economic impact assessment to identify wider relevance and possible resource-sharing, and 3. consistent integration of environmental considerations. Economic analysis offers a congruent measure of value complementing diverse impact metrics among sectors and contexts.